Generalized pustular psoriasis and Cushing’s syndrome in childhood due to corticosteroids misuse - Azizah, Fitri; Rahman, Yusnita; Rihatmadja, Rahadi; Agustin, Triana; Astriningrum, Rinadewi; Rahmayunita, Githa (UI Scholars Hub, 2021)
Background: Generalized pustular psoriasis (GPP) is characterized clinically by yellowish sterile pustules surrounded by erythema. GPP in children is very rare and may appear following steroid withdrawal in psoriasis vulgaris.Case Illustration: A 14-year-old female presented to the emergency unit with generalized erythematous plaques and multiple pustules with lake of pus after abruptly stopped oral and topical corticosteroid for two weeks. The patient had used topical and oral corticosteroids for almost a year to treat psoriasis. Physical examination revealed moderately ill and tachycardic, with short stature, moon face, amenorrhea, and multiple erythematous plaques with multiple pustules and lake of pus along with red-purple striae all over the body.Discussion: Adverse effects of steroid-induced adrenal insufficiency are time-dependent and generally reversible. Gradual discontinuation of steroids must adhere to physiological dose of steroids, mostly in 3.49 ± 2.92 months. Other treatments available are emollients, salicylic acid, calcipotriol, coal tar, topical steroids, phototherapy, retinoids, and cyclosporine. Topical steroids cannot be the main therapy in severe psoriasis due to the possible side effects of excessive usage. Conclusion: Misuse of topical and systemic steroid in children could lead to Cushing’s syndrome, a multisystem disorder resulting from prolonged exposure to excess glucocorticoids, either both systemic or topical. Children could easily develop systemic reactions to topical steroids due to their higher total body surface area to body weight ratio.